Порівняльний аналіз реагентів для комплексної обробки чавуну - Кисляков, Володимир Геннадійович; Молчанов, Лавр Сергійович; Маначин, Іван Олександрович; Похвалітий, Артем Анатолійович; Чубіна, О. А. (ДДТУ, Кам’янське, 2024)
UKR: Метою даної роботи є узагальнення результатів застосування різних реагентів для комплексного видалення домішок з рідкого чавуну. Випробувано використання плаву соди як реагенту на промисловому рівні в 140-тонному чавуновозному ковші, а також наведено результати експериментальних обробок. Розглянуто технологію комплексного рафінування чавуну з використанням системи реагентів CaO-FeO-Na2CO3, яка базується на взаємодії зазначених компонентів із рідким чавуном. Описано можливі хімічні перетворення, що відбуваються під час введення цих реагентів, зокрема реакції десульфурації, окиснення та видалення шкідливих домішок. За результатами лабораторних досліджень на «гарячій» моделі було проведено аналіз поведінки домішок та побудовано картограми впливу компонентів реагентів на видалення фосфору, сірки та кремнію. Також побудовано потрійні діаграми стану для системи CaO-FeO-Na2CO3, що дозволило зробити висновки щодо оптимальних умов для комплексного рафінування чавуну.

ENG: The aim of this work is to summarize the results of using various reagents for the comprehensive removal of impurities from molten cast iron. A comparative analysis of the effectiveness of different reagents for cast iron refining was conducted. The use of soda slag as a reagent was tested at the industrial level in a 140-ton hot metal ladle, and the results of experimental treatments were presented. A technology for comprehensive cast iron refining using the CaO-FeO-Na2CO3 reagent system was considered, which is based on the interaction of these components with molten cast iron. Possible chemical transformations occurring during the introduction of these reagents were described, including desulfurization reactions, oxidation, and the removal of harmful impurities. Based on laboratory studies using a "hot" model, an analysis of impurity behavior was conducted, and influence maps of the reagents' components on phosphorus, sulfur, and silicon removal were constructed. Additionally, ternary phase diagrams for the CaO-FeO-Na2CO3 system were developed, which helped to determine optimal conditions for comprehensive cast iron refining. The results of an industrial test of soda ash as a reagent for complex cast iron refining confirmed that this material is effective for the simultaneous removal of sulfur, silicon and phosphorus under certain conditions. Laboratory and industrial studies have shown that a multi-stage impurity removal process during the out-of-furnace cast iron treatment — oxygen converter shop process link is an effective approach for comprehensive cast iron refining. In particular, at the out-of-furnace treatment stage, effective sulfur removal is achieved by using desulphurization reagents, followed by additional silicon and phosphorus removal at the BOF stage. The use of sodium carbonate (Na2CO3) in combination with other reagents such as CaO and FeO has shown significant potential for complex cast iron refining. The combinations of these components have demonstrated high efficiency in removing both sulfur and phosphorus, which allows optimizing the technological process of cast iron refining. Other reagents or technological solutions may be required to achieve a higher degree of silicon removal at the out-of-furnace iron treatment stage. The analysis of the behavior of impurities and chemical reactions during the treatment process shows that the introduction of additional reducing agents, such as aluminum, can help reduce the negative impact of CO2 and increase the efficiency of impurity removal. The constructed mapping and state diagrams demonstrated that changing the proportions of the components of the CaO-FeO-Na2CO3 system allows achieving different degrees of sulfur, silicon, and phosphorus removal, which makes it possible to select the optimal composition of the refining mixture for each specific case. The research results show that the CaO-FeO-Na2CO3-Al mixture is suitable for complex cast iron refining under laboratory test conditions and can be effectively used for the simultaneous removal of several harmful impurities. Increasing the amount of aluminum leads to a deterioration in refining performance from silicon and phosphorus.
Comparative Analysis of Reagents for Complex Treatment of Cast Iron
В. Кисляков: ORCID 0000-0002-1775-5050; Л. Молчанов: ORCID 0000-0001-6139-5956; І. Маначин: ORCID 0000-0001-9795-6751; А. Похвалітий: ORCID 0000-0002-9652-767Х; О. Чубіна: ORCID 0000-0003-2213-5013
Keywords: чавун; реагент; домішки; позапічна обробка; порівняння; cast iron; reagent; impurities; out-of-furnace treatment; comparison; КАВП; TECHNOLOGY::Chemical engineering::Metallurgical process and manufacturing engineering